The Truth Matters: A Citizen's Guide to Separating Facts from Lies and Stopping Fake News in Its Tracks - Bruce Bartlett (Ten Speed Press, 2017)
Todayâ€™s media and political landscapes are littered with untrustworthy sources and the dangerous concept of â€œfake news.â€ This accessible guide helps you fight this deeply troubling trend and ensure that truth is not a permanent casualty. Written by Capitol Hill veteran and author Bruce Bartlett, The Truth Matters presents actionable tips and tricks for reading critically, judging sources, using fact-checking sites, avoiding confirmation bias, identifying trustworthy experts, and more.